2015
DOI: 10.2174/1876396001508010043
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a D-aspartic Acid/Sodium Nitrate/Vitamin D3 Dietary Supplement on Physiological Parameters in Middle-aged Men: A Pilot Study

Abstract: D-aspartic acid (DAA), nitrate, and vitamin D 3 have received considerable attention in recent years for their potential health-enhancing properties. Using an open-label design, we evaluated the impact of a DAA/sodium nitrate/ vitamin D 3 dietary supplement on blood testosterone and nitrate/nitrite, as well as subjective indicators of health, in middle-aged men.Methods: 10 overweight or obese men (mean age: 42 years) were assigned to ingest a DAA/sodium nitrate/ vitamin D 3 supplement (either one or two servin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…It is similar finding by Bloomer et al and Willoughby et al and contrary to the study of Topo et al (40, 49, 50). Baseline testosterone levels of the current study were higher than values found in Topo et al and Bloomer et al experiments (6.3, 4.5 and 3 ng/mL respectively), so one can say that baseline testosterone levels may have no effect on influence of D-Asp supplementation that was previously assumed.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…It is similar finding by Bloomer et al and Willoughby et al and contrary to the study of Topo et al (40, 49, 50). Baseline testosterone levels of the current study were higher than values found in Topo et al and Bloomer et al experiments (6.3, 4.5 and 3 ng/mL respectively), so one can say that baseline testosterone levels may have no effect on influence of D-Asp supplementation that was previously assumed.…”
Section: Resultssupporting
confidence: 85%
“…The authors hypothesized that 6 gr of D-Asp per day may affect negative feedback mechanisms of the HPG axis, thus reducing pituitary initiated production of luteinizing hormone and also testosterone levels. However, in the study of Bloomer et al , 6 gr daily of D-Asp had no effect on the testosterone levels (50). …”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…However, repeating this protocol over a 12-week training period did not result in any changes in T concentration [ 21 ]. The literature also includes some studies reporting an increase in T concentration in men supplemented with DAA; however, the subjects in these groups were characterized by low baseline T concentration in the blood [ 13 , 19 , 20 ]. The average baseline T concentrations in these studies (9–16 nmol/L) were lower than those observed in our present study (13.9–25.1 nmol/L—baseline), as well as in previous studies that did not confirm the beneficial effects of DAA (18–41 nmol/L) [ 14 , 15 , 16 , 17 , 18 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Supplementation began four days before the first exposure to hypoxia and continued throughout the whole of the LH–TL training period. D-aspartic acid (DAA) dose and supplementation time were selected based on the methodologies of previous studies regarding the ergogenic effects of DAA [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Methodsmentioning
confidence: 99%